2009
DOI: 10.1002/jor.20898
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and chondrogenic differentiation of mesenchymal cells from adipose tissue of different species

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells capable of differentiating into several mesoderm lineages. They have been isolated from different tissues, such as bone marrow, adult peripheral blood, umbilical cord blood, and adipose tissue. The aim of this study was to analyze the differences in proliferation and phenotype of adipose tissue-derived MSCs from three different species, and to evaluate their capacity to differentiate into chondrocytes in vitro. A comparative study of cultured human, rabbit, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 48 publications
7
63
0
1
Order By: Relevance
“…This result agrees with the findings of others in equine MSCs (9), being coexpressed by more than the 92% of the cells (10). A high percentage of MSCs from other species such as canine, ovine, or porcine also display in their cell surface these molecules (11)(12)(13).…”
supporting
confidence: 92%
“…This result agrees with the findings of others in equine MSCs (9), being coexpressed by more than the 92% of the cells (10). A high percentage of MSCs from other species such as canine, ovine, or porcine also display in their cell surface these molecules (11)(12)(13).…”
supporting
confidence: 92%
“…CD44 is a hyaluronate receptor. The positive staining for CD44 antibody in flow cytometry argued with that published by Barry et al (1999) and Martínez et al (2009). These studies showed that CD44 is an antibody that characterizes mesenchymal cells for human and sheep fat tissue derived cells.…”
Section: Discussionsupporting
confidence: 61%
“…As in equine MSCs, CD 29 and CD 44 expressions are found consistently in canine (34,35,51,52), ovine (53), and porcine (54) MSCs. Corresponding to the equine antigen expression profile as well, CD 73 could not be detected in canine, rabbit, or sheep MSCs (35,55,56), while rat tendon derived, feline and bovine neonatal cell sources and caprine bone marrow-derived MSCs expressed this antigen (57)(58)(59)(60). CD 73 protein expression could also be detected in bone marrow derived MSCs from mice but only in moderate amounts (61).…”
Section: Discussionmentioning
confidence: 92%